Kawasaki Disease Following Severe Sunburn Injury - Seigo Okada; Seigo Okada; Shintaro Hashimoto; Akiko Miyake; Yusuke Okada; Reiji Hirano; Shinnosuke Fukunaga; Yuichi Ishikawa (Frontiers Media S.A., 2020)
Background: Although an etiology of Kawasaki disease (KD) is unknown, an aberrant innate immune system in predisposed individuals has been proposed to play a key role in the development of KD vasculitis. Various etiological pathogens have been proposed as the trigger of KD and a scaled injury preceding symptom onset has been reported as one of them. Here, we report a 17-month-old Japanese female who was hospitalized due to high fever lasting for 4 days with infection ruled out as a cause. On admission, she displayed severe sunburn all over her body following a prolonged period of outdoor play 5 days ago. On the 5 day of illness, she developed complete KD. Serum levels of high mobility group box 1, a representative for damage-associated molecular patterns (DAMPs), were elevated during acute phase and continued to decrease during subacute phase. This unique course suggested the inflammatory process of KD involving innate immunity via DAMPs.